2018
DOI: 10.3892/ol.2018.8524
|View full text |Cite
|
Sign up to set email alerts
|

MIIP gene expression is associated with radiosensitivity in human nasopharyngeal carcinoma cells

Abstract: Abstract. The present study aims to investigate the radiosensitization effect of the migration and invasion inhibitory protein (MIIP) gene on nasopharyngeal carcinoma (NPC) cells. The MIIP gene was transfected into NPC 5-8F and CNE2 cells. The level of MIIP was analyzed by quantitative reverse transcription-polymerase chain reaction analysis and western blot. The changes in radiosensitivity of the cells were analyzed by colony formation assay. The changes in cell apoptosis and cycle distribution following irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Apoptosis is associated with radiosensitivity; increased apoptosis indicates elevated radiosensitivity (4850). Numerous molecules and pathways are involved in apoptotic processes, including the mitochondria, which serve key roles (5153).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is associated with radiosensitivity; increased apoptosis indicates elevated radiosensitivity (4850). Numerous molecules and pathways are involved in apoptotic processes, including the mitochondria, which serve key roles (5153).…”
Section: Discussionmentioning
confidence: 99%
“…MIIP was characterized by its role in inhibiting migration and invasion in glioma, and hence the name. Since the identification of MIIP [ 2 ], a limited number of studies addressed the function and mechanism of MIIP in tumorigenesis, with most of them indicate MIIP plays inhibitory effects on tumorigenesis in many types of cancer [ 6 – 9 , 14 , 31 34 ]. Besides, a few study also reported opposite effects of MIIP.…”
Section: Discussionmentioning
confidence: 99%
“…There are selected genotypes that promote radiosensitivity and are associated with various clinical conditions. The migration and invasion inhibitory protein gene expression is associated with radiosensitivity in human nasopharyngeal carcinoma cells [51]. Melanoma cells have been reported to demonstrate a heterogeneous range of radiosensitivity and are radiosensitized by inhibition of proto-oncogene B-RAF [52].…”
Section: Strengths Of Tbddmentioning
confidence: 99%